Blues : its birth and growth - Elmer, Howard (New York : Rosen Pub. Group, 1999)
Traces the origins of blues music, its evolution in the United States, and its influence on jazz and rock and roll
Discography: p. 58-59
Includes bibliographical references (p. 60-61) and index
Keywords: Blues (Music) -- History and criticism -- Juvenile literature; Blues (Music) -- History and criticism